Effect of Cohesion and Shear Modulus on the Stability of a Stretched Granular Layer - Melo-Hurtado, F (2012)
The main mechanism of the cellular pattern which forms at the surface of a thin layer of a cohesive granular material submitted to in-plane stretching has been identified as the "strain softening" arising from the features of grain-grain interactions. We perform measurements of the strain field associated with such structures by using a correlation image technique and additionally characterize the cohesion and shear modulus of the samples. We show that for high cohesion, the layer is fragile and the surface deformation is highly nonlinear, whereas at low cohesion, a smooth and linearly growing structure is observed as a function of external stretching. Analysis of the wavelength as a function of cohesion along with independent measurement of the shear modulus indicate that a simple model of strain softening is acceptable if a mechanism of cluster formation due to cohesion is taking place. © 2012 American Physical Society.